If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x+15=-4x+28
We move all terms to the left:
5x+15-(-4x+28)=0
We get rid of parentheses
5x+4x-28+15=0
We add all the numbers together, and all the variables
9x-13=0
We move all terms containing x to the left, all other terms to the right
9x=13
x=13/9
x=1+4/9
| x^2-12x+36-81=0 | | 2x^2+58=10 | | 0.4c=220 | | f(-3)-3f(1)=-16 | | 2w+w=600 | | 2s2-8=0 | | 10.4=d/2 | | x^2-20x+100-1=0 | | 10^-2=3x+5 | | 2y+3y=-6 | | -n+5=21n=0 | | 2f(2)+f(4)=21 | | 6x+9=7(x-6) | | 2/3x+4=1/2-2x | | 6-(2n-3)=2n+3 | | √x+3-x=-4 | | √x-3-x=-4 | | 3m+4=4m+2 | | (4x-16)(4x-1)=0 | | 3m=4=4m+2 | | (a+1)(a-9)=0 | | 3y=8y-85 | | 3y=5y-24 | | 16-5x=22-3x | | 13-8x=28-5x | | 4+x/9=5 | | 0=(x-1)(2x+7) | | 3^2x=19 | | 5t+3=2t15 | | M=2n-7 | | -2x^2-20x+5=0 | | 36)10=j/6 |